(untitled) (Journal of Enam Medical College, 2012)
Background: Repeated blood transfusion is the main life line support for thalassaemic children and so they are more prone to be infected with HBV. In Bangladesh the main source of blood for transfusion is the professional donors and so the possibility of HBV infection is higher. Objective: To assess the frequency of HBV among children who received more than 3 blood transfusions. Materials and Methods: This cross sectional analytical study was conducted in Pediatrics ward of Bangabandhu Sheikh Mujib Medical University, Dhaka during the period of July 2003 to June 2004. Ninety five children aged less than 15 years, suffering from ? thalassaemia major and Hb E ? thalassaemia having blood transfusion more than three times and 20 controls of similar age and sex were included in this study. Seromarkers of HBV were tested and the results were analyzed using SPSS version Windows 11.0. Results: Out of 115 children 68 were ? thalassaemic (mean age 6.8 ± 2.84 yrs and male:female is 4.2:1), 27 were Hb E ? thalassaemic children (mean age 8.78 ± 2.99 yrs and M:F 1.4:1) and 20 were nontransfused, age and sex matched controls (mean age 6.23 ± 1.88 yrs and M:F 1:2.3). Out of 95 thalassaemic children 21 (22.1%) were positive for HBsAg. Among them 13 were ? thalassaemic and 8 were Hb E ? thalassaemic. None of the controls showed HBsAg positivity indicating a significant statistical difference (p=0.033). 28 (29.5%) children were positive for anti-HBc. Among them 23 were ? thalassaemic and 5 were Hb E ? thalassaemic and there was no core antigen positivity among the controls showing a significant statistical difference (p=0.022). Four (4.2%) patients showed HBeAg positivity, out of whom 3 were ? thalassaemic and 1 was Hb E ? thalassaemic. But this antigen was not found in any control and thereby, no statistical significant difference was observed (p=0.637). Among 20 controls, 2 were positive for anti-HBe antibody, but none of the thalassaemic children was positive for this antibody showing statistically significant difference (p=0.008). Conclusion: A significantly higher sero-prevalence of hepatitis B viral marker was observed among the multitransfused thalassaemic children. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12838 J Enam Med Col 2012; 2(2): 56-61